Integration of integrated Islamic school curriculum into Kurikulum Merdeka - Rahmat Rahmat; Dinn Wahyudin; Laksmi Dewi (Himpunan Pengembang Kurikulum Indonesia, 2024)
Integrated Islamic Schools (SIT) is a unique entity specifically born in Indonesia at the same time as the Nurul Fikri Integrated Islamic Elementary School in Depok in 1993. This school model developed rapidly until 2003 when the Integrated Islamic Schools Network was declared, and more than 1000 schools were established throughout Indonesia. This research discusses the stages and layers in developing a typical curriculum for Integrated Islamic Schools. The research results show that integrated Islamic schools organize themselves, including organizing the curriculum to align with all applicable rules and regulations in Indonesia. On the other hand, it aligns with the established institutional vision. In this way, integrated Islamic schools carry out a curriculum development process. This development process is carried out through various stages and layers, namely through conceptual aspects to realize belief in the creator, aspects of subject matter containing religious knowledge (kauliyah) and worldly knowledge (kauniyah), as well as integration in implementation to create education that is academic, spiritual, ethics, and social. Abstrak Integrated Islamic Schools merupakan entitas unik yang secara spesifik lahir di Indonesia bersamaan dengan hadirnya Sekolah Dasar Islam Terpadu Nurul Fikri di Depok pada tahun 1993. Model sekolah ini berkembang pesat, hingga tahun 2003 saat Jaringan Integrated Islamic Schools dideklarasikan telah tercatat lebih dari 1000 sekolah berdiri di seluruh Indonesia. Penelitian ini bertujuan untuk membahas tentang tahapan dan lapisan yang dimaksud dalam konteks pengembangan kurikulum khas Integrated Islamic Schools. Hasil penelitian menunjukan bahwa sekolah islam terpadu melakukan penataan dirinya termasuk menata kurikulum agar sejalan dengan seluruh peraturan dan ketentuan yang berlaku di Indonesia dan disisi lain sejalan dengan visi kelembagaan yang didirikan. Dengan demikian maka sekolah islam terpadu melakukan proses pengembangan kurikulum. Proses pengembangan ini dilakukan melalui berbagai tahapan dan lapisan, yaitu melalui aspek konseptual untuk mewujudkan keyakinan kepada pencipta, aspek materi pelajaran yang mengandung ilmu agama (kauliyah) maupun ilmu duniawi (kauniyah), serta integrasi dalam implementasi untuk menciptakan pendidikan yang bersifat akademis, spiritual, etika, dan sosial. Kata Kunci: Integrated Islamic Schools; kurikulum merdeka; kurikulum nasional; kurikulum terpadu; pengembangan kurikulum